SOMEONE HELP ASAPPPPPPPPP
![SOMEONE HELP ASAPPPPPPPPP class=](https://us-static.z-dn.net/files/d39/550335149c34e96f6002a70f4c81c415.png)
Answer:
D = [tex]f^{-1}(x) = 4(x+12)[/tex] = [tex]f^{-1}(x) = 4x+48[/tex]
Step-by-step explanation:
First, replace f(x) with y, and switch x and y:
[tex]y = \frac{1}{4}x-12[/tex]
[tex]x = \frac{1}{4}y-12[/tex]
Now, solve for y again:
[tex]x+12=\frac{1}{4}y[/tex]
[tex]y = 4(x+12)[/tex]
Replace y with correct inverse function notation, and you have your answer:
[tex]f^{-1}(x) = 4(x+12)[/tex]